An Autoregressive Distributed Lag (ARDL) Model Approach for Nigerian GDP, Exchange Rate and Foreign Import Trade - Aliyu Chamalwa, Hamidu; Abbas, Muhammad; Abdulsalam, Bashir; Yunusa Baba, Luqman (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study examined the relationship between GPD and Exchange Rate, Foreign Trade using ARDL approach. The data used for the study was obtained from the CBN statistical Bulletin. The test of stationarity performed on the variables indicated that they are all on stationary at levels and the order of integration are (2), (1) and (1) for GDP, exchange rate and Foreign Trade respectively. The results revealed that a long-run relationship between foreign import trade, GDP and foreign exchange. The speed of adjustment to equilibrium; when there was a shift and suggested that it could take about 86.3% of previous years for it to return to a stable state. The study recommended that government should strengthen foreign exchange policies, foreign trade for sustained economic growth.